A Spatial Analysis of Florida County Governments' Unreserved General Fund Balances. (25th April 2017) - Guo, Hai (David); Wang, Wen
Abstract : The most recent Great Recession brought our attention to the issue of fiscal sustainability of local governments. Local governments often rely on their general fund balances to deal with contingencies and economic downturns. Empirical research, however, produces mixed results and is inconclusive about what determines the size of local savings. No previous research on this topic has considered strategic interactions and the spatial relationship among local governments. Using a panel dataset of all the county governments in Florida from 2007 to 2011, this study examines the factors that affect the size of unreserved fund balances and empirically tests the spatial effects concerning local fund balance policies in Florida. Empirical findings indicate the importance of the spillover effects of a county's millage rate change and reliance on intergovernmental transfers. This research contributes to the literature by accounting for the spatial effects in local fund balance behavior.